Ca2+-dependent regulation of sodium channels NaV1.4 and NaV1.5 is controlled by the post-IQ motif - Jesse B. Yoder (Nature Portfolio, 2019)
Skeletal muscle voltage-gated Na+ channel (NaV1.4) activity is subject to calmodulin (CaM) mediated Ca2 +-dependent inactivation while cardiac NaV1.5 is not. Here authors use structural biology, binding and electrophysiology to parse the Ca2 +-dependent changes of CaM when bound to the NaV1.4.